Physical activity and neuroplasticity in neurodegenerative disorders: a comprehensive review of exercise interventions, cognitive training, and AI applications - Ben Ezzdine, Lamia; Dhahbi, Wissem; Dergaa, Ismail; Ceylan, Halil İbrahim; Guelmami, Noomen; Ben Saad, Helmi; Chamari, Karim; Stefanica, Valentina; El Omri, Abdelfatteh (Frontiers in Neuroscience, 2025)
This review aimed to elucidate the mechanisms through which (i) physical activity (PA) enhances neuroplasticity and cognitive function in neurodegenerative disorders, and (ii) identify specific PA interventions for improving cognitive rehabilitation programs. We conducted a literature search in PubMed, Medline, Scopus, Web of Science, and PsycINFO, covering publications from January 1990 to August 2024. The search strategy employed key terms related to neuroplasticity, physical exercise, cognitive function, neurodegenerative disorders, and personalized physical activity. Inclusion criteria included original research on the relationship between PA and neuroplasticity in neurodegenerative disorders, while exclusion criteria eliminated studies focusing solely on pharmacological interventions. The review identified multiple pathways through which PA may enhance neuroplasticity, including releasing neurotrophic factors, modulation of neuroinflammation, reduction of oxidative stress, and enhancement of synaptic connectivity and neurogenesis. Aerobic exercise was found to increase hippocampal volume by 1–2% and improve executive function scores by 5–10% in older adults. Resistance training enhanced cognitive control and memory performance by 12–18% in elderly individuals. Mind–body exercises, such as yoga and tai-chi, improved gray matter density in memory-related brain regions by 3–5% and enhanced emotional regulation scores by 15–20%. Dual-task training improved attention and processing speed by 8–14% in individuals with neurodegenerative disorders. We also discuss the potential role of AI-based exercise and AI cognitive training in preventing and rehabilitating neurodegenerative illnesses, highlighting innovative approaches to personalized interventions and improved patient outcomes. PA significantly enhances neuroplasticity and cognitive function in neurodegenerative disorders through various mechanisms. Aerobic exercise, resistance training, mind–body practices, and dual-task exercises each offer unique cognitive benefits. Implementing these activities in clinical settings can improve patient outcomes. Future research should focus on creating personalized interventions tailored to specific conditions, incorporating personalized physical exercise programs to optimize cognitive rehabilitation.